2010
DOI: 10.1097/inf.0b013e3181b99fa2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Azithromycin 1.5% Eye Drops for Purulent Bacterial Conjunctivitis in Pediatric Patients

Abstract: Azithromycin 1.5% eye drops leads to a rapid clinical and microbiological cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
3
21
0
1
Order By: Relevance
“…However, the bacteriological profile for patients in this study is similar to the one determined in the paediatric subgroup of an earlier large randomised controlled study17 20 and consistent with the causative microorganisms usually found in the literature for acute conjunctivitis in young children21–23. Haemophilus influenzae was the most frequently isolated pathogen, probably owing to the high incidence of associated acute otitis media in children with bacterial conjunctivitis (reported in 20–73% of cases), as this bacteria is the predominant pathogen responsible for the conjunctivitis otitis syndrome24–26.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, the bacteriological profile for patients in this study is similar to the one determined in the paediatric subgroup of an earlier large randomised controlled study17 20 and consistent with the causative microorganisms usually found in the literature for acute conjunctivitis in young children21–23. Haemophilus influenzae was the most frequently isolated pathogen, probably owing to the high incidence of associated acute otitis media in children with bacterial conjunctivitis (reported in 20–73% of cases), as this bacteria is the predominant pathogen responsible for the conjunctivitis otitis syndrome24–26.…”
Section: Discussionsupporting
confidence: 88%
“…When compared with tobramycin, efficacy of azithromycin was found to be significantly superior on D3 and non-inferior on D7. The clinical cure rates obtained for both antibiotics are very similar to those of previous studies, that is, 48% on D3 and 80% on D9 in azithromycin-treated children compared with 27% and 82% in tobramycin-treated children (6 years old on average)17 20.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Clinical trials demonstrated superior bacteriological cure with azithromycin treatment compared with treatment with tobramycin [39,40]. Fusidic acid is frequently prescribed by general practitioners.…”
Section: Bacterial Conjunctivitismentioning
confidence: 99%
“…Treatment is requested, because it provides eradication of the bacteria and more rapid clinical improvement, decreases the rate of reinfection, prevents the invasion of infection, provides relief of the sypmtoms, shortens the disease time and decreases the risk of development of complications which threaten vision (28,(30)(31)(32)(33)(34). Ophtalmic antibiotics which are administered for a shorter period and with simpler doses increase the efficiency of treatment (35).…”
Section: Acute Bacterial Conjunctivitismentioning
confidence: 99%